Evaluation of Groundwater for Arsenic Contamination Using Hydrogeochemical Properties and Multivariate Statistical Methods in Saudi Arabia - Abdullah S. Al-Farraj; Mohammad I. Al-Wabel; Mohamed Hamza El-Saeid; Ahmed H. El-Naggar; Zaheer Ahmed (Journal of Chemistry)
The aim of this research is to evaluate arsenic distribution and associated hydrogeochemical parameters in 27 randomly selected boreholes representing aquifers in the Al-Kharj geothermal fields of Saudi Arabia. Arsenic was detected at all sites, with 92.5% of boreholes yielding concentrations above the WHO permissible limit of 10 μg/L. The maximum concentration recorded was 122 μg/L (SD = 29 μg/L skewness = 1.87). The groundwater types were mainly Ca+2-Mg+2-SO4-2-Cl− and Na+-Cl−-SO4-2, accounting for 67% of the total composition. Principal component analysis (PCA) showed that the main source of arsenic release was geothermal in nature and was linked to processes similar to those involved in the release of boron. The PCA yielded five components, which accounted for 44.1%, 17.0%, 10.1%, 08.4%, and 06.5% of the total variance. The first component had positive loadings for arsenic and boron along with other hydrogeochemical parameters, indicating the primary sources of As mobilization are derived from regional geothermal systems and weathering of minerals. The remaining principal components indicated reductive dissolution of iron oxyhydroxides as a possible mechanism. Spatial evaluation of the PCA results indicated that this secondary mechanism of arsenic mobilization may be active and correlates positively with total organic carbon. The aquifers were found to be contaminated to a high degree with organic carbon ranging from 0.57 mg/L to 21.42 mg/L and showed high concentrations of NO3- ranging from 8.05 mg/L to 248.2 mg/L.